Trastuzumab duocarmazine in locally advanced and metastatic solid tumours and HER2-expressing breast cancer: a phase 1 dose-escalation and dose-expansion study. Issue 8 (August 2019) - Banerji, Udai; van Herpen, Carla M L; Saura, Cristina; Thistlethwaite, Fiona; Lord, Simon; Moreno, Victor; Macpherson, Iain R; Boni, Valentina; Rolfo, Christian; de Vries, Elisabeth G E; Rottey, Sylvie; Geenen, Jill; et al.
Summary: Background: Trastuzumab duocarmazine is a novel HER2-targeting antibody–drug conjugate comprised of trastuzumab covalently bound to a linker drug containing duocarmycin. Preclinical studies showed promising antitumour activity in various models. In this first-in-human study, we assessed the safety and activity of trastuzumab duocarmazine in patients with advanced solid tumours. Methods: We did a phase 1 dose-escalation and dose-expansion study. The dose-escalation cohort comprised patients aged 18 years or older enrolled from three academic hospitals in Belgium, the Netherlands, and the UK with locally advanced or metastatic solid tumours with variable HER2 status who were refractory to standard cancer treatment. A separate cohort of patients were enrolled to the dose-expansion phase from 15 hospitals in Belgium, the Netherlands, Spain, and the UK. Dose-expansion cohorts included patients aged 18 years or older with breast, gastric, urothelial, or endometrial cancer with at least HER2 immunohistochemistry 1+ expression and measurable disease according to Response Evaluation Criteria in Solid Tumors (RECIST). Trastuzumab duocarmazine was administered intravenously on day 1 of each 3-week cycle. In the dose-escalation phase, trastuzumab duocarmazine was given at doses of 0·3 mg/kg to 2·4 mg/kg (3 + 3 design) until disease progression or unacceptable toxicity. The primary endpoint of the dose-escalation phase was to assess safety and ascertain the recommended phase 2 dose, which would be the dose used in the dose-expansion phase. The primary endpoint of the dose-expansion phase was the proportion of patients achieving an objective response (complete response or partial response), as assessed by the investigator using RECIST version 1.1. This ongoing study is registered withClinicalTrials.gov, numberNCT02277717, and is fully recruited. Findings: Between Oct 30, 2014, and April 2, 2018, 39 patients were enrolled and treated in the dose-escalation phase and 146 patients were enrolled and treated in the dose-expansion phase. One dose-limiting toxic effect (death from pneumonitis) occurred at the highest administered dose (2·4 mg/kg) in the dose-escalation phase. One further death occurred in the dose-escalation phase (1·5 mg/kg cohort) due to disease progression, which was attributed to general physical health decline. Grade 3–4 treatment-related adverse events reported more than once in the dose-escalation phase were keratitis (n=3) and fatigue (n=2). Based on all available data, the recommended phase 2 dose was set at 1·2 mg/kg. In the dose-expansion phase, treatment-related serious adverse events were reported in 16 (11%) of 146 patients, most commonly infusion-related reactions (two [1%]) and dyspnoea (two [1%]). The most common treatment-related adverse events (grades 1–4) were fatigue (48 [33%] of 146 patients), conjunctivitis (45 [31%]), and dry eye (45 [31%]). Most patients (104 [71%] of 146) had at least one ocular adverse event, with grade 3 events reported in ten (7%) of 146 patients. No patients died from treatment-related adverse events and four patients died due to disease progression, which were attributed to hepatic failure (n=1), upper gastrointestinal haemorrhage (n=1), neurological decompensation (n=1), and renal failure (n=1). In the breast cancer dose-expansion cohorts, 16 (33%, 95% CI 20·4–48·4) of 48 assessable patients with HER2-positive breast cancer achieved an objective response (all partial responses) according to RECIST. Nine (28%, 95% CI 13·8–46·8) of 32 patients with HER2-low, hormone receptor-positive breast cancer and six (40%, 16·3–67·6) of 15 patients with HER2-low, hormone receptor-negative breast cancer achieved an objective response (all partial responses). Partial responses were also observed in one (6%, 95% CI 0·2–30·2) of 16 patients with gastric cancer, four (25%, 7·3–52·4) of 16 patients with urothelial cancer, and five (39%, 13·9–68·4) of 13 patients with endometrial cancer. Interpretation: Trastuzumab duocarmazine shows notable clinical activity in heavily pretreated patients with HER2-expressing metastatic cancer, including HER2-positive trastuzumab emtansine-resistant and HER2-low breast cancer, with a manageable safety profile. Further investigation of trastuzumab duocarmazine for HER2-positive breast cancer is ongoing and trials for HER2-low breast cancer and other HER2-expressing cancers are in preparation. Funding: Synthon Biopharmaceuticals.